Fabrication of CVD duplicate diamond microgear. Issue 182 (24th July 2017) - Wei, Liu; Wenzhuang, Lu; Hongjun, Wang; Jing, Pang
ABSTRACT: CVD diamond is an ideal processing material which is suitable for the Micro-Electro-Mechanical System parts, such as microgears, for its excellent performance. In this article, the masks for duplicate diamond microgear deposition have been etching through ICP technology. Meanwhile, the duplicate diamond microgears with teeth number of 20 and 14 were deposited in the corresponding silicon mold cavity by HFCVD method. The gears were fabricated successfully and analyzed by SEM and metalloscope. The result shows that the ICP-CVD process is able to fabricate duplicate diamond microgears in batches with flat surface, high shape and size consistency and position accuracy.